Differences in gene expression profile between vocal cord Leukoplakia and normal larynx mucosa by gene chip - Jianhua Peng; He Li; Jun Chen; Xianming Wu; Tao Jiang; Xiaoyun Chen (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Long non-coding RNAs (lncRNAs) play an important role in tumorigenesis. Vocal cord leukoplakia is a precancerous lesion in otolaryngological practice. Till now, the expression patterns and functions of lncRNAs in vocal cord leukoplakia have not been well understood. In this study, we used microarrays to investigate the aberrantly expressed lncRNAs and mRNAs in vocal cord leukoplakia and adjacent non-neoplastic tissues. Methods Gene Ontology and pathway analyses were performed to determine the significant function and pathways of the differentially expressed mRNAs. qRT-PCR was performed to further validate the expression of selected lncRNAs and mRNAs in vocal cord leukoplakia. Results Our study identified 170 differentially expressed lncRNAs and 99 differentially expressed mRNAs, including 142 up-regulated lncRNAs and 28 down-regulated lncRNAs, and 54 up-regulated mRNAs and 45 down-regulated mRNAs. Among these, XLOC_000605 and DLX6-AS1 were the most aberrantly expressed lncRNAs. Furthermore, we identified an antisense lncRNA (LOC100506801), an enhancer-like lncRNA (AK057351) and three long intergenetic noncoding RNAs including XLOC_008001, XLOC_011989 and XLOC_007341. Conclusions Our results revealed that many lncRNAs were differentially expressed between vocal cord leukoplakia tissues and normal tissue, suggesting that they may play a key role in vocal cord leukoplakia tumorigenesis.